Fabrication, Properties, and Biomedical Applications of Calcium-Containing Cellulose-Based Composites - Shi, Ru-Jie; Lang, Jia-Qi; Wang, Tian; Zhou, Nong; Ma, Ming-Guo (Frontiers in Bioengineering and Biotechnology, 2022)
Calcium-containing cellulose-based composites possess the advantages of high mechanical strength, excellent osteoconductivity, biocompatibility, biodegradation, and bioactivity, which represent promising application system in the biomedical field. Calcium-containing cellulose-based composites have become the hotspot on the study of various biomedical fields. In this mini-review article, the synthesis of calcium-containing cellulose-based composites is summarized via a variety of methods such as biomimetic mineralization method, microwave method, co-precipitation method, hydrothermal method, freeze-drying method, mechanochemical reaction method, and ultrasound method. The development on the fabrication, properties, and applications of calcium-containing cellulose-based composites are highlighted. The as-existed problems and future developments of cellulose-based composites are provided. It expects that calcium-containing cellulose-based composites are ideal candidate for biomedical application.